Above all, be kind : raising a humane child in challenging times - Weil, Zoe (New Society Publishers, 2003)
Above All, Be Kind teaches parents how to raise their children to be humane in the broadest sense -- to become not only more compassionate in their interactions with family and friends, but to grow up to make life choices that demonstrate respect for the environment, other species, and all people. The book includes chapters for early, middle, teenage, and young adult years, as well as activities, issue sidebars, cases, tips, and profiles.